PENGARUH PENGGUNAAN HEWAN UJI YANG SAMA SECARA BERULANG PADA PENGUJIAN KOROSI DERMAL - Retno Puji Lestari; Andriantoro Andriantoro (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2018)
One of the procedures to determine the hazardous and toxic material waste is by conducting the corrosive testing. The testing of waste toxicity by acute dermal method is applied to recognize the adverse effects that occur after exposing the waste by direct contact. It will be indicated by corrosive or irritated effects, either topically or locally. Dermal corrosion testing is conducted under OECD Guideline no 404 using rabbit. Unknown waste sample and detergent as positive control were exposed to the shaved-dorsal part of rabbit with the area of 2.5 x 2.5 cm. Observation was performed to recognize the symptom of oedema and erythema as a result of sample’s reaction with skin and was being evaluated after 4, 24, 48, and 72 hours. In this study, dermal corrosion testing was performed using the same test animal due to animal welfare issues about reducing animal in toxicology study. The visual scoring result showed that waste sample did not generate the corrosive effect on animal test. The experiment using detergent sample are intended to obtain some information after the assessment of corrosive level. The testing with the same animal was carried out after 30 days later. The first test presented the category 3, mild irritant, with the average score for erythema/edema of 2,1, while the second testing showed category 4, non irritant. Thus, using same individual testing animal on repeated dermal corrosion testing showed the effect of resistance to detergent samples and the animal provided a less-sensitive respond for the same sample.